Isolation, structural characterization and neuraminidase inhibitory activities of polyphenolic constituents from Flos caryophylli. (March 2017) - He, Zining; Lian, Wenwen; Liu, Jiawei; Zheng, Runsheng; Xu, Hui; Du, Guanhua; Liu, Ailin
Graphical abstract: Highlights: Two new flavonoids have been isolated from Flos. Caryophylli . The isolated polyphenolic constituents inhibited influenza neuraminidase. The isolated compounds exhibited anti-influenza activity and low cytotoxicity. Abstract: Neuraminidase (NA) is one of the key surface proteins of the influenza virus, which is an important target for anti-influenza therapy. In the present study, bioassay-guided fractionation led to isolation of two new compounds, rhamnetin-3- O -β-d -glucuronide-6″-methyl ester (1 ) and rhamnazin-3- O -β-d -glucuronide-6″-methyl ester (2 ), along with seventeen known compounds (3 -19 ), from the MeOH extract of Flos Caryophylli using in vitro NA inhibition assay. These isolated compounds exhibited significantly inhibitory effects on the NA with IC50 values ranging from 8.4 to 94.1 μM and were found to protect MDCK cells from A (H1N1) influenza infections (EC50 = 1.5–84.7 μM) with very low cytotoxicity to the host cells (CC50 = 374.3–1266.9 μM)), with selective index (SI) ranging from 7 to 297. The primary structure-relationships of these isolates were also discussed.